AI for Intelligent Customer Service: How Salesforce Einstein is Automating Customer Support - Bajjuru, Rohit; Kacheru, Goutham; Arthan, Nagaraju (BULLET : Jurnal Multidisiplin Ilmu, 2022)
This paper focuses on the importance of Artificial Intelligence in Customer Relationship Management and how Salesforce Einstein GPT helps in managing our customer relations. This research, taking a qualitative approach using literature review and cases from Spotify and KONE examines how the companies profited by having Salesforce Einstein implementation. The research examines how AI can improve different areas of CRM such as customized customer experiences, predictive analytics and sales process optimization. OUTCOMES: Realizing the benefits of AI enabled CRM solutions in your organization for better customer interactions and relationship management.